Broadband and high-contrast-ratio optical diodes based on polarization conversion and photonic bandgap. (7th June 2018) - Wu, Xiaohu; Fu, Ceji
Abstract: We propose to realize a broadband and high-contrast-ratio optical diode by using a layered structure composed of uniaxial crystal slabs with differently oriented optical axes. The operation principle is based on polarization conversion combined with photonic bandgap. Our numerical results show that an optical diode can be realized with the transmissivity contrast ratio higher than 10 000 in the wavelength range from 0.567 to 0.636 μ m by using hexagonal boron nitride slabs for the structure. Theoretically, this method is suitable for any anisotropic materials, and the geometric parameters of the structure can be adjusted to tune the wavelength range as well as the transmissivity contrast ratio of the optical diode. Therefore, our work may provide useful guidelines to the design of compact broadband and high-contrast-ratio optical diodes.